Cell transformation by fibroblast growth factors can be suppressed by truncated fibroblast growth factor receptors. - Li, Y (1994)
Ligand-induced dimerization and transphosphorylation are thought to be important events by which receptor tyrosine kinases generate cellular signals. We have investigated the ability of signalling-defective, truncated fibroblast growth factor (FGF) receptors (FGFR-1 and FGFR-2) to block the FGF response in cells that express both types of endogenous FGF receptors. When these dominant negative receptors are expressed in NIH 3T3 cells transformed by the secreted FGF-4, the transformed properties of the cells can be reverted to various degrees, with better reversion phenotype correlating with higher levels of truncated receptor expression. Furthermore, truncated FGFR-2 is significantly more efficient at producing reversion than FGFR-1, indicating that FGF-4 preferentially utilizes the FGFR-2 signalling pathway. NIH 3T3 clones expressing these truncated receptors are more resistant to FGF-induced mitogenesis and also exhibit reduced tyrosine phosphorylation upon treatment with FGF. The block in FGF-signalling, however, can be overcome by the addition of excess growth factor. The truncated receptors have binding affinities that are four- to eightfold lower than those of wild-type receptors, as measured by Scatchard analysis. We also observed a partial specificity in the responses of truncated-receptor-expressing clones to FGF-2 or FGF-4. Our results suggest that the block to signal transduction produced by kinase-negative FGF receptors is achieved through a combination of dominant negative effects and competition for growth factor binding with functional receptors.